New Tools, Pathways, and Challenges That Address the Crisis of Antimicrobial Resistance - Vinall, Phil (MD Conference Express, 2014)
Despite the dangers associated with increased resistance, the rate of new antibiotic development has been decreasing over the last 30 years. This article reviews the recent multipronged efforts to address these issues via support for research and development, enhancement of regulatory pathway options that permit progression via smaller programs, and development of innovative options for antibiotic business models.